KEKERASAN VERBAL PADA TAYANGAN PESBUKERS ANTV PASCA TEGURAN KPI MARET 2018 - Mutiara, Wahyu; Alit Suryawati, I Gusti Agung; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2021)
Pesbukers is the most favourite and most watched comedy program. Beside all the achievement that they got, Pesbukers have a lot of controversial issues such as putting verbal abuse in their content. Even though they have received several reprimands from KPI, Pesbukers still re-airing and still do not change the violent content in it. This research’s main problem is how verbal violence contents appears in the Pesbukers for one episode on February 12, 2019. In this study the author uses the Stuart Hall representation theory to see how Pesbukers represent violence. For this study verbal violence is analysed based on 4 categorizations, first is Insulting/harassing/demeaning certain community groups; second is Associating humans to animals/inanimate objects; third is Crude expressions/curse/threats; and last one is Insulting someone physically or body shaming. This study found 36 in total repetitions of verbal violence in just one episode. Keyword : representation, verbal violation, Pesbukers as a comedy program.